Implementation of lead users into management practice: A literature review of publications in business press - Jens Lehnen; Daniel Ehls; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2014)
Integrating lead users into the product development process is a promising source of innovations. While the lead user approach is clearly established in academia, the implementation into management practice is ambiguous. Conducting a literature review of 255 articles in business press we show the diffusion in praxis and analyze coherency to the academic perspective. We derive propositions and identify inconsistencies to the current theoretical understanding, particularly regarding the definition, identification process and methods. We reveal latest developments in praxis and provide a basis for the adaptation of the classical lead user approach.
Keywords: 330; lead user; diffusion; adoption; practical implementation; business press review